Modelling clinical progression and health care utilization of HIV‐positive patients in British Columbia prior to death. Issue 9 (18th March 2014) - Cui, Z; Grafstein, E; Yip, B; Hogg, R; Montaner, JSG; Lima, VD
<x xml:space="preserve">Abstract</x> Objectives The extent to which clinical progression of HIV‐positive patients leads to an increase in health care utilization, especially prior to their death, is unknown. Thus, we modelled trends in CD4 cell count and emergency department utilization and the likelihood of an emergency department visit leading to a transfer to an acute care‐level facility prior to a patient's death from nonaccidental causes. Methods Eligible patients initiated highly active antiretroviral therapy (HAART) in British Columbia between August 1996 and June 2006 (n = 457). Patients were followed until their death, which occurred on or before 30 June 2007 (period in which the emergency department visit data were available). Trends were modelled using generalized mixed effects. Results Patients experienced a significantly steep decline in CD4 cell count and a corresponding increase in the number of emergency department visits and transfers to acute‐level facilities in the 5 years prior to death. For every 6‐month interval prior to death, the CD4 cell count decreased by 13.22 cells/μL, the risk of experiencing an emergency department visit increased by 9%, and among those ever admitted, the odds ratio of being transferred to an acute care‐level facility increased by 3%. Conclusions We showed that patients experienced a steep decline in CD4 cell count, which was associated with an increase in health care utilization prior to their death. These findings highlight the substantial residual avoidable burden that unsuccessfully managed HIV disease poses, even in the HAART era. Further strategies to enhance sustained and successful engagement in care are urgently needed to mitigate high health care utilization.